2011
DOI: 10.1016/j.str.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Antagonists Bind through a Short Peptide to the First β-Propeller Domain of LRP5/6

Abstract: The Wnt pathway inhibitors DKK1 and sclerostin (SOST) are important therapeutic targets in diseases involving bone loss or damage. It has been appreciated that Wnt coreceptors LRP5/6 are also important, as human missense mutations that result in bone overgrowth (bone mineral density, or BMD, mutations) cluster to the E1 propeller domain of LRP5. Here, we report a crystal structure of LRP6 E1 bound to an antibody, revealing that the E1 domain is a peptide recognition module. Remarkably, the consensus E1 binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
194
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(214 citation statements)
references
References 59 publications
(98 reference statements)
20
194
0
Order By: Relevance
“…5E). The ability of the peptides used in this study to inhibit Wnt1 signaling was unexpected in the light of a report by Bourhis et al (36), suggesting that similar peptides did not inhibit Wnt9B binding to LRP6 (which, similar to Wnt1, has been proposed to bind to the first propeller of LRP5/6). To investigate this further, we attempted to stimulate canonical Wnt signaling in our reporter cell line with Wnt9B.…”
Section: Asn-93 Of Sclerostin Plays Key Role In Its Ability To Interamentioning
confidence: 53%
“…5E). The ability of the peptides used in this study to inhibit Wnt1 signaling was unexpected in the light of a report by Bourhis et al (36), suggesting that similar peptides did not inhibit Wnt9B binding to LRP6 (which, similar to Wnt1, has been proposed to bind to the first propeller of LRP5/6). To investigate this further, we attempted to stimulate canonical Wnt signaling in our reporter cell line with Wnt9B.…”
Section: Asn-93 Of Sclerostin Plays Key Role In Its Ability To Interamentioning
confidence: 53%
“…Structural analysis of the LRP5 protein revealed that all amino acids involved in any of the HBM are clustered at an open binding pocket near the surface of the first b-propeller of LRP5 (119). The mutations do not have any effect on the functioning of the protein but rather disrupt the ligand binding of the extracellular inhibitors DKK1 and sclerostin (120,121,122), in which a short binding motif was found by structure analysis (123). The latter protein was identified by positional cloning for two other sclerosing bone disorders, Van Buchem disease and sclerosteosis (124,125,126,127).…”
Section: Identification Of the Role Of The Lrp5 Gene In Bonementioning
confidence: 97%
“…The remaining Wnts have not been tested in these assays. The top surfaces of P1 and P3 (and P2 and P4 as well) do not harbor N-glycosylation sites (Ahn et al 2011;Bourhis et al 2011;Chen et al 2011;Cheng et al 2011) and are likely the Wnt-binding interface. Indeed, missense substitutions of multiple top surface residues of P3 of LRP6, designed based on the crystal structure, diminish or enhance Wnt3a binding and signaling ( Fig.…”
Section: Two or More Wnt-binding Surfaces Of Lrp6mentioning
confidence: 99%